4
$\begingroup$

I was solving questions on beta and gamma functions and then I came across this question.

$$ \int_0^1 \frac{(1-x^4)^{3/4}}{(1+x^4)^2}\,dx $$

Generally in questions of beta functions integrals of the type $\int x^n(1−x^m) \, dx$ can be solved by substituting $x^m = t$, but in this case substitution is unconventional because if I put $1+x^4=t$, then I will not get the required form of beta function

I tried substituting $x^2 = \tan t$ and also tried substituting $x^2 = \cos t$ but on simplifying each of them further I could not reduce them to standard form of beta function.

$\endgroup$
13
$\begingroup$

Apply the substitution $x^4 = \frac{1-u}{1+u}$. Then

$$ I := \int_{0}^{1} \frac{(1-x^4)^{3/4}}{(1+x^4)^2} \, dx = \frac{1}{2^{9/4}} \int_{0}^{1} u^{3/4}(1-u)^{-3/4} \, du = \frac{1}{2^{9/4}} B(\tfrac{7}{4},\tfrac{1}{4}) = \frac{3\pi}{2^{15/4}}.$$


Explanations. First substitute $x^4 = t$ to obtain $ I = \frac{1}{4} \int_{0}^{1} \frac{(1-t)^{3/4}t^{-3/4}}{(1+t)^2} \, dx$. To transform this integral into the form of beta integral, we notice that

  • $-1$, $0$ and $1$ are the only branch points/poles of the integrand,
  • $0$, $1$, $\infty$ are the only branch points/poles of the integrand of $\int_{0}^{1} u^{\alpha-1}(1-u)^{\beta-1} \, du$.

This leads to consider a Möbius transformation $t = f(u) = \frac{au+b}{cu+d}$ satisfying either

  1. $f(\infty) = -1$, $f(0) = 0$ and $f(1) = 1$ and $ad-bc > 0$, or
  2. $f(\infty) = -1$, $f(0) = 1$ and $f(1) = 0$ and $ad-bc < 0$.

The first condition yields $f(u) = \frac{u}{2-u}$ and the second condition yields $f(u) = \frac{1-u}{1+u}$. Both can be used, since one condition is simply transformed to the other by $z \mapsto 1-z$.

$\endgroup$
  • 2
    $\begingroup$ (+1) Nice substitution! I tried a different approach using the binomial theorem a couple of times. $\endgroup$ – robjohn Sep 24 '18 at 6:32
7
$\begingroup$

We can use the Binomial Theorem in the form $$ (1+x)^{-\alpha}=\sum_{k=0}^\infty\frac{(-1)^k\Gamma(k+\alpha)}{\Gamma(\alpha)\Gamma(k+1)}x^k\tag1 $$ to get $$ \begin{align} \int_0^1\frac{(1-x^4)^{3/4}}{(1+x^4)^2}\,\mathrm{d}x &=\frac14\int_0^1\frac{(1-x)^{3/4}}{(1+x)^2}x^{-3/4}\,\mathrm{d}x\tag2\\ &=\frac14\int_0^1(1-x)^{3/4}x^{-3/4}\sum_{k=0}^\infty(k+1)(-x)^k\,\mathrm{d}x\tag3\\ &=\frac14\sum_{k=0}^\infty(-1)^k(k+1)\int_0^1(1-x)^{3/4}x^{k-3/4}\,\mathrm{d}x\tag4\\ &=\frac14\sum_{k=0}^\infty(-1)^k(k+1)\frac{\Gamma\!\left(\frac74\right)\Gamma\left(k+\frac14\right)}{\Gamma(k+2)}\tag5\\ &=\underbrace{\frac14\Gamma\!\left(\frac74\right)\Gamma\!\left(\frac14\right)\vphantom{\sum_{k=0}^\infty}}_{\frac{3\sqrt2}{16}\pi}\underbrace{\sum_{k=0}^\infty\frac{(-1)^k\Gamma\left(k+\frac14\right)}{\Gamma\left(\frac14\right)\Gamma(k+1)}}_{(1+1)^{-1/4}}\tag6\\ &=\frac{3\sqrt[4]2}{16}\pi\tag7 \end{align} $$ Explanation:
$(2)$: substitute $x\mapsto x^{1/4}$
$(3)$: apply $(1)$ with $\alpha=2$ and use $(k+1)\Gamma(k+1)=\Gamma(k+2)$
$(4)$: collect the integral for the Beta Function
$(5)$: evaluate the integral
$(6)$: rearrange factors and use $(k+1)\Gamma(k+1)=\Gamma(k+2)$
$(7)$: $\frac14\Gamma\!\left(\frac74\right)\Gamma\!\left(\frac14\right) =\frac14\cdot\frac34\Gamma\!\left(\frac34\right)\Gamma\!\left(\frac14\right) =\frac3{16}\pi\csc\left(\frac\pi4\right) =\frac{3\sqrt2}{16}\pi$
$\phantom{(7)\text{:}}$ apply $(1)$ with $\alpha=\frac14$ and $x=1$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.